Staff Development through Team and Competency Building - Umoh, Olivia (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
Abstract The study is a summary of the activities in change project to improve staff development through team building and competency building among the staff of a nonprofit organization in Ghana. The nonprofit is in the mission of developing streetchildren by giving them a better quality of life. The set of interventions that were conducted effected immediate observable changes in the team during the short duration of the study. Due to the initial success, the study is still in progress and monitored in terms of delivery. Keywords: staff development , team building, competency building, non profit, organizational effectiveness